Resistance to airflow and moisture loss of table grapes inside multi-scale packaging - Ngcobo, Mduduzi Elijah Khulekani (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD(Agric))--Stellenbosch University, 2013.